Unforgiven - Daniels, B. J. (Harlequin HQR Romantic suspense, 2012)
When Destry Grant's brother is accused of killing Rylan West's sister, high school sweethearts Destry and Rylan leave their relationship behind in order to help their families recover from tragedy.